PENGARUH LABA KOTOR DAN KOMPONEN ARUSKAS TERHADAP HARGA SAHAM - Riswanto; Abdillah, Muhammad Abi; Gultom , Selfi Afriani (Politeknik Negeri Medan, 2024)
This research aims to determine the effect of profit and cash flow information on stock prices. The variables cash flow from operating activities, cash flow from investment activities, cash flow from financing activities and gross profit are the independent variables and share price is the dependent variable. The number of samples used in this research was 40 basic industry and chemical subsector companies listed on the Indonesia Stock Exchange from 2016 to 2019. This research uses secondary data. Data was collected using a purposive sampling method based on certain conditions. Data were analyzed using a linear regression model. The results of this study show that cash flow from investing activities and gross profit have an effect on stock prices, while cash flow from operating activities and cash flow from financing activities have no effect on stock prices.